eCM 2012
DOI: 10.22203/ecm.v023a08
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and catabolic signalling in intervertebral discs: The roles of NF-B and MAP Kinases

Abstract: Painful intervertebral disc disease is characterised not only by an imbalance between anabolic (i.e., matrix synthesis) and catabolic (i.e., matrix degradation) processes, but also by infl ammatory mechanisms. The increased expression and synthesis of matrix metalloproteinases and infl ammatory factors is mediated by specifi c signal transduction, in particular the nuclear factor-kappaB (NF-B) and mitogen-activated protein kinase (MAPK)-mediated pathways. NF-B and MAPK have been identifi ed as the master reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
198
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(209 citation statements)
references
References 141 publications
7
198
0
1
Order By: Relevance
“…Furthermore, phosphorylation of NF-B is sustained (Ͼ30 min), which agrees with other studies that have found prolonged NF-B activation in NP and AF cells (46,47). For other pathologies, both p38 (rheumatoid arthritis) and NF-B (atopic dermatitis) inhibitors have gone to clinical trials (45). If successful, these inhibitors may also positively affect disc degeneration.…”
Section: Tlr2 Regulates Ngf Via Nf-bsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, phosphorylation of NF-B is sustained (Ͼ30 min), which agrees with other studies that have found prolonged NF-B activation in NP and AF cells (46,47). For other pathologies, both p38 (rheumatoid arthritis) and NF-B (atopic dermatitis) inhibitors have gone to clinical trials (45). If successful, these inhibitors may also positively affect disc degeneration.…”
Section: Tlr2 Regulates Ngf Via Nf-bsupporting
confidence: 88%
“…As expected, the downstream signal mechanisms are similar and include the NF-B pathway and p38, ERK1/2, and JNK MAP kinase signaling, which can cause a variety of transcription factors to translocate to the nucleus (10,30). Activation of these pathways in discs results in an increase in inflammatory mediators and proteases (45). Although signaling mechanisms of TLR2 have been extensively investigated in other cell types, they are only now being elucidated in intervertebral disc.…”
Section: Tlr2 Regulates Ngf Via Nf-bmentioning
confidence: 58%
“…Inappropriate activation of NFKB has been associated with numerous inflammatory diseases (30). Wuertz et al (32) have reported that IDD is characterized not only by an imbalance between anabolic and catabolic processes, but also by inflammatory mechanisms. Of note, IL-1β and TNF-α are pro-inflammatory cytokines, which have been detected in the degenerated disc (33).…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the fact that pain perception comprises a complex series of neurophysiologic events involving stimulation, tissue response, transmission of pain signal and subsequent modulation of these at both peripheral and central levels (Ito and Creemers, 2013;Schaible, 2012). Inflammatory cytokines are important regulators of these pain mechanisms and their presence is associated with inflammatory pain arising from articular joints and IVDs (Ito and Creemers, 2013;Wuertz et al, 2012;Zhang et al, 2013). Interleukin-1 beta (IL-1β) and tumour necrosis factor alpha (TNF-α) contribute to disease progression and pain, by acting directly not only as nociceptive triggers, but also by inducing generation of other potentially nociceptive molecules, including nitric oxide and prostaglandin E (Liu et al, 2016;.…”
Section: Trpml2 -/-mentioning
confidence: 99%